The Effect of Job Placement, Compensation, and Work Environtment on Work Spirit through Job Satisfaction - Suhindra Agustian; Yadi Maryadi (Penerbit Goodwood, 2026)
Purpose: This study analyzes the direct effects of job placement, material compensation, and the work environment on employee work spirit, and examines whether job satisfaction mediates these relationships uniformly or differentially across antecedents, using the Department of Public Works and Spatial Planning of Pagar Alam City as the empirical setting.Research Methodology: A quantitative associative survey was conducted involving all 93 employees using saturated (census) sampling. Data were collected through Likert-scale questionnaires, transformed using the Method of Successive Interval, and analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS) in SmartPLS 3.Results: Job placement, material compensation, and the work environment each had positive and significant direct effects on both job satisfaction and work spirit. Job satisfaction also positively affected work spirit and emerged as the strongest predictor. It did not significantly mediate the effects of job placement or material compensation, indicating direct-only relationships, but significantly and complementarily mediate the effect of the work environment on work spirit.Conclusions: Employee work spirit is influenced primarily by the direct effects of placement, compensation, and the work environment, while job satisfaction mediates only the environmental pathway, indicating differentiated mediation across antecedents.Limitations: The study was limited to a single public institution and employed a cross-sectional, single-source design. Common method bias was not formally tested.Contributions: This study provides empirical evidence of differentiated mediation, showing that job satisfaction mediates only the work environment–work spirit relationship, thereby offering practical guidance for public-sector human resource management.